Alternate energy sources and environmental quality: The impact of inflation dynamics - Bilal; Khan, Irfan; Tan, Duojiao; Azam, Waseem; Tauseef Hassan, Syed (Gondwana research, 2022)
[Display omitted] •Impact of alternative energy sources on environmental quality checked.•Advanced econometric methodologies applied for empirical analysis.•Alternative energy sources are negatively associated with the ecological footprint.•Government expenditures and inflation improve environmental quality in the long-run.•Economic growth deteriorates environmental quality in the long-run. In the past few years, the investigation into the case of ecological footprint and its determining factors has remained the core subject of debate among policy analysts. But some of the crucial determinants of ecological footprint have not been sufficiently covered in the literature. This study employed government expenditures, inflation dynamics, and economic growth from 1971 to 2016 as moderator variables to examine the impact of alternative energy sources on Germany’s environmental quality. We applied advanced econometric methodologies for empirical analysis. The results of fully modified least squares, dynamic least squares, and robust canonical cointegrating regressions indicate that alternative energy sources, government expenditures, and inflation are negatively associated while economic growth is positively associated with the environmental quality in Germany. Policymakers are encouraged to eliminate subsidies for domestic coal productions, promote cost-efficient ecological policy designs, price environmental resources, intensify green budget, decouple economic growth from the harmful emissions, and generate a trade-off between stabilizing inflation and stabilizing fluctuations through a sustainable monetary policy.